(untitled) (TEST Ticontre. Theory Text Translation, 2022)
Among the dits of Guillaume de Machaut consecrated to animal figures, the Dit dou lyon deserves a new ecdotic and critical study. It is a narrative work dating back to 1342, consisting of more than two thousand octosyllabes and transmitted by eleven manuscripts (14th-15th centuries), which contain Machaut’s works and almost all accompanied by a rich iconographic apparatus. Indeed, the two manuscripts that do not keep miniatures are however prepared to receive them, as proof of the importance of the iconographic element in the process of making manuscripts containing the works of Guillaume de Machaut, then to their reception and “monumentalization”. This article reflects on the nature of the text-image relationship in the illuminated manuscripts of the Dit dou lyon and in particular the analysis is aimed at pursuing an objective: through a collation of the miniatures and their mise en page, an attempt will be made to highlight the existence of any relationships between the manuscripts, to be supported by the ecdotic data obtainable from the readings of the manuscripts and from a material-philological analysis.